Detection of Resistance Genes (Blandm and Blavim) of Escherichia Coli in the Aquatic Environment - Mahdi, Zinah Mohammed; Hatif, Zainab Hani; Younis , Mohammed Hassan; Abed Allah, Roaa Abed Almunaam (Iraqi Journal of Science, 2023)
The study aims to detect the presence of carbapenems genes and the prevalence of antibiotic-resistant E. coli in the Tigris River. Samples were collected from three sites of the Tigris River: S1Adhamiya, S2 Medical city hospital, and S3 Abu Nuwas. It diagnosed 40 isolates of E. coli out of 67 isolates of bacteria by Vitek2. The antibiotic sensitivity was determined by the disk diffusion method. E.coli isolates were tested against 7 antibiotics these belonged to β-lactam, Carbapenem. Also, the resistance genes) blaVIM and blaNDM) detected for these isolates of E. coli.  The results appeared resistance of  E.coli against AMC 82.5%, PRL 62.5%, AM 55%, and moderate resistance against  CRO 45% whereas little resistance against ATM 27.5%  and carbapenem  including IPM 5%and MRP 5%. Also, the results of resistance genes have appeared in two isolates that have the resistance gene blaVIM (5%) and one isolate has blaNDM genes (2.5%). These isolates appeared resistant to β-lactam group antibiotics and little resistance to E. coli to carpamenes antibiotics (IMP, MER).